Impact of Perceived Organizational Support on Innovative Work Behavior and Burn out in Teachers: Thriving at Work as the Mediator (2020) (Journal of Education and Educational Development, 2023)
This study explores the interaction of four major factors at the workplace, namely, perceived organizational support, burnout, thriving at work and innovative work behavior, specifically in the setting of the private high schools of Karachi. The study looks at why some instructors in the same organization succeed under trying circumstances such as those engendered by the Covid 19 situation, while others struggle and eventually succumb to burnout. Data consists of responses of 196 teachers, collected through a questionnaire on Likert scale and SPSS is used for analysis. Results show that perceived organizational support has a positive impact on innovative work behavior, whereas burnout is negatively impacts teachers. It has been demonstrated that thriving at work is a powerful mediator.